Two educational-cultural issues by the Spanish libertarian anarchism in the French exile (1945) - Viñao Frago, Antonio (Historia y Memoria de la Educación, 2019)
This paper will present, contextualize, comment on and transcribe two leaflets on educational-cultural issues ― dated in 1945 and produced and published by the Spanish libertarian anarchism in the French exile ―. The first, the Essays on the Organization of National Education, was written by the Freinetist teacher, José de Tapia y Bujalance (1896-1989). From the second, the Memoir of the Local Federations Congress held in Paris from 1 to 12 May 1945, we transcribe only the «Decision corresponding to the section f) of point 9 that deals with the cultural and educational national order», and the «Decision corresponding to point 22 that deals with the Control of the Press and Propaganda»